I, VOLKSWAGEN. Issue 2 (22nd June 2021) - Collins, Stephanie
Abstract: Philosophers increasingly argue that collective agents can be blameworthy for wrongdoing. Advocates tend to endorse functionalism, on which collectives are analogous to complicated robots. This is puzzling: we don't hold robots blameworthy. I argue we don't hold robots blameworthy because blameworthiness presupposes the capacity for a mental state I call 'moral self-awareness'. This raises a new problem for collective blameworthiness: collectives seem to lack the capacity for moral self-awareness. I solve the problem by giving an account of how collectives have this capacity. The trick is to take seriously individuals' status as flesh-and-blood material constituents of collectives. The idea will be: under certain conditions that I specify, an individual can be the locus of a collective's moral self-awareness. The account provides general insights concerning collectives' dependence on members, the boundaries of membership, and the locus of collectives' phenomenology.